A survey of unmanned aerial sensing solutions in precision agriculture. (15th December 2019) - Mukherjee, Anandarup; Misra, Sudip; Raghuwanshi, Narendra Singh
Abstract: We attribute the gain in popularity of Unmanned Aerial Vehicles (UAV), Platforms and Systems (UAS) to its ease of operation, versatility, and risk-free piloting. The primary UAV application domain has expanded from recreational and military flights to include scientific surveys and agriculture. The popularity of UAVs in scientific data gathering and applications, especially the use of small multi-rotor UAVs is quite widespread. These portable multi-rotor UAVs are portable, low-cost, highly maneuverable, and easy to handle. These features make such UAVs attractive to scientists and researchers worldwide. There has been a sudden spurt of UAV use in niche domains such as agriculture. Agriculturalists are choosing UAV-based field operations and remote sensing over the time-tested satellite-based ones, especially for local-scale and high spatiotemporal resolution imagery. In this survey, we explore various UAV application areas, types, sensors, research domains, and deployment architectures. We provide comparisons between various UAV types, sensing technologies (UAV, WSN, satellites), UAV architectures, and their utility in precision agriculture. Finally, we outline the challenges and the future scope of such UAV-based solutions for precision agriculture.